Calcium reduction of stingray (Himantura gerrardi) bones with EDTA disodium salt assisted ultrasound - Priyosetyoko Priyosetyoko; Meiny Suzery; Widayat Widayat (E3S Web of Conferences)
Calcium reduction of bone is crucial to collagen purification and gelatin synthesis from fish bones. Research on the effect of immersion time on the reduction of calcium products assisted by ultrasound at 950 W 25 kHz on the bones of Himantura gerrardi stingrays has been carried out. This study used 0.1 M EDTA disodium salt as a chelating agent to form complex Ca-EDTA compounds with variations in immersion time for 0, 2, 4, 6, 10, 16, 18, 20, 22, and 24 hours. The results of X-ray fluorescence (XRF) analysis showed that soaking for 24 hours produced calcium at a level of 1.16%, which was the lowest level in this research. The results of the analysis using the Fourier transform infrared spectroscopy (FTIR) instrument have detected amide A, amide B, amide I, amide II, and amide III at 3275, 2920, 1634, 1541, and 1240 cm-1, respectively. In addition, a typical wave absorption has been found in the fingerprint region 1021 and 559 cm-1, similar to the vibrational characteristics of PO³⁻ in hydroxyapatite compounds. This study has shown the potential for stingray bone waste to be used for the purification of bone collagen and to produce hydroxyapatite.